Additive manufacturing of 18% nickel maraging steels: Defect, structure and mechanical properties: A review. (1st September 2022) - Guo, Lulu; Zhang, Lina; Andersson, Joel; Ojo, Olanrewaju
Highlights: The recent advances in the additive manufacturing of maraging steels are reviewed. Various defects are formed with the use of inappropriate processing parameters. Different techniques contribute to forming different molten pool profiles. Distinct precipitation behaviors are observed during different techniques. Mechanical properties of the additive manufactured and wrought parts are compared. Abstract: This paper reviews the latest research progress in the additive manufacturing (AM) process of 18% nickel maraging steels, which involves laser-based powder bed fusion (L-PBF), laser-based directed energy deposition (L-DED), and wire arc additive manufacturing (WAAM). The emphasis is on the defects, structure, and mechanical properties of the additive manufactured 18% nickel maraging steels. At first, this article outlines the influences of the processing parameters of AM techniques on the defects formed in the fabricated parts, in terms of the L-PBF and WAAM. The macrostructure and microstructure characteristics of as-built and heat-treated 18% nickel maraging steel are then described in detail. Later, the mechanical properties of as-built and heat-treated 18% nickel maraging steel are assessed, such as their tensile, hardness, impact toughness, and fatigue performances. Finally, future directions for work on the AM of 18% nickel maraging steel are provided. Abstract : Image, graphical abstract .